Comparison of V̇o2peak and V̇o2max at Different Sampling Intervals in Collegiate Wrestlers. Issue 10 (18th October 2021) - Sell, Katie M.; Ghigiarelli, Jamie J.; Prendergast, James M.; Ciani, Gioia J.; Martin, Jacob; Gonzalez, Adam M.
Abstract: Sell, KM, Ghigiarelli, JJ, Prendergast, JM, Ciani, GJ, Martin, J, and Gonzalez, AM. Comparison of V̇o 2 peak and V̇o 2 max at different sampling intervals in collegiate wrestlers. J Strength Cond Res 35(10): 2915–2917, 2021—The purpose of this study was to determine the difference in the highest oxygen uptake (V̇o 2 peak) achieved during a maximal effort graded exercise test (GXT) in 20 NCAA Division I male wrestlers using breath-by-breath (BbB) values to the maximal uptake averaged across different time- and breath-based oxygen consumption sampling intervals (V̇o 2 max). Given the need for aerobic fitness and anaerobic power in wrestling, the accurate determination of V̇o 2 max is imperative if it is to be used to identify current aerobic fitness and consequently guide sport-specific training programs to address weaknesses in this area. Each subject completed a cycle ergometer GXT during which BbB data were collected via indirect calorimetry and V̇o 2 peak determined as the highest value. V̇o 2 max was considered as the average value of 3-s, 5-s, 10-s, 20-s, and 30-s sampling, and 3-b, 7-b, and 11-b sampling during the GXT. Results show that the BbB V̇o 2 peak was significantly higher than the 5-s, 10-s, 20-s, 30-s, and 11-b ( p < 0.05). The 3-b V̇o 2 max was significantly higher than the 20-s and 30-s V̇o 2 max values ( p < 0.05). The underestimation of V̇o 2 peak for each time-based interval sampling approach compared with BbB V̇o 2 peak is consistent with previous research, but the comparison of BbB data to breath-based interval sampling has not been widely addressed in prior research. The use of a 7-b sampling interval for the determination of V̇o 2 max may be a promising approach to minimize the systematic errors associated with BbB or less frequent sampling intervals, but future research is needed to further support its application with elite athletic populations such as those in the current study.